Health Administration In Emergency Medicine: Evaluating Emergency Care Systems In Saudi Arabia (The Review of Diabetic Studies, 2025)
Saudi Arabia’s healthcare system has made significant strides over the last few decades, particularly in the domain of emergency medical services (EMS). However, challenges related to accessibility, workforce shortages, and the overall quality of care, especially in rural areas, continue to hinder optimal care delivery. This paper evaluates the emergency care systems in Saudi Arabia, highlighting the strengths, challenges, and ongoing reforms in the healthcare infrastructure, workforce development, access to emergency services, and the effectiveness of government policies. By analysing recent developments and offering strategic recommendations, this study contributes to enhancing the delivery of emergency care, ensuring greater equity and quality for all citizens.